2011
DOI: 10.1097/shk.0b013e3181ea45ca
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Cd14 and Cd36 Expression, Bacterial Clearance, and Toll-Like Receptor 4-Myd88 Signaling in Caveolin-1-Deleted Macrophages and Mice

Abstract: An overwhelming immune response, particularly from macrophages, with gram-negative bacteria-induced sepsis plays a critical role in survival of and organ damage in infected patients. Caveolin-1 (Cav-1), a major structure protein of caveolae, regulates many cellular functions. We examined the vital role of Cav-1 in the response of macrophages and mice to bacteria or LPS exposure. Deletion of Cav-1 decreased the expression of CD14 and CD36 during macrophage differentiation and suppressed their phagocytotic abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 34 publications
3
59
0
Order By: Relevance
“…One potential route of internalization of CD36 is the caveolae-dependent pathway used by TLR receptors (196). Studies showing that caveolin-1 (Cav1) gene disruption is associated with altered subcellular localization and function of CD36 (169,219) are consistent with this hypothesis. When the oral LCFA levels become sufficient to allow the binding and activation of GPR120 in lipid raft (149) triggers the GLP-1 release by TBC (121,149) (FIGURE 8, 4).…”
Section: Indirect Cooperation Hypothesissupporting
confidence: 66%
“…One potential route of internalization of CD36 is the caveolae-dependent pathway used by TLR receptors (196). Studies showing that caveolin-1 (Cav1) gene disruption is associated with altered subcellular localization and function of CD36 (169,219) are consistent with this hypothesis. When the oral LCFA levels become sufficient to allow the binding and activation of GPR120 in lipid raft (149) triggers the GLP-1 release by TBC (121,149) (FIGURE 8, 4).…”
Section: Indirect Cooperation Hypothesissupporting
confidence: 66%
“…Then, the upper layer was removed and the lymphocyte layer was transferred according to the manufacturer's instructions. The lymphocytes were lysed with 0.1% saponin for 15 min, serially diluted, plated onto LB agar plates, and incubated at 37°C for 18 h. CFUs of bacteria were determined by the number of colonies formed [21].…”
Section: Animal Proceduresmentioning
confidence: 99%
“…This receptor complex is expressed on numerous cell types, including cells of the immune system and parenchymal cells (9). Studies using mouse strains deficient in TLR4 signaling (10)(11)(12), TLR4 expression (10,(13)(14)(15)(16), or using inhibitors of TLR function in wild type (WT) mice (1,17) confirmed that TLR4 contributes to bacterial clearance and the host inflammatory response in the setting of Gram-negative bacterial infection. Furthermore, the TLR4 Asp 299 Gly polymorphism, which results in depressed LPS-TLR4 signaling (18), is associated with increased susceptibility to Gramnegative infections in humans (19).…”
mentioning
confidence: 99%